2015
DOI: 10.3329/bccj.v3i1.24093
|View full text |Cite
|
Sign up to set email alerts
|

In-hospital prognostic value of on admission creatinine clearance in patients with acute coronary syndrome

Abstract: Objective: To find out association between creatinine clearance rate (CCR) and in-hospital outcome of acute coronary syndrome (ACS).Methodology: This prospective observational study was carried on 100 patients with acute coronary syndrome, in Coronary Care Unit (CCU) of BIRDEM General Hospital, Shahbag, Dhaka, over a period of six months from July 1, 2012 to December 31, 2012.Results: Subjects were divided into three groups (A:CCR>60,B :CCR-30-60and C:CCR<30) depending on their CCR (ml/min). Mean creatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 31 publications
(29 reference statements)
2
0
0
Order By: Relevance
“…Similar study done by Madurima et al, 10 included 100 patients of ACS and divided into three groups as in our study and found that mortality in group A was 0, group B was 5.7% and group C was 8.8% with p-value 0.001. This study also shows that mortality increase as the renal function worsens.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Similar study done by Madurima et al, 10 included 100 patients of ACS and divided into three groups as in our study and found that mortality in group A was 0, group B was 5.7% and group C was 8.8% with p-value 0.001. This study also shows that mortality increase as the renal function worsens.…”
Section: Discussionsupporting
confidence: 87%
“…Similar study done by Madhurima Saha et al 10 found that subjects had hypertension (64%), dyslipidaemia (51%) and diabetes mellitus (46%). No significant difference was observed among the three groups.…”
Section: Discussionsupporting
confidence: 77%